Kearifan Lingkungan Desa dalam Novel Indonesia Mutakhir: Kajian Ekokritik Sastra - Nova Agusryana Syarif (Balai Bahasa Provinsi Riau, 2022)
Natural aspect has become an object that authors always discuss in literary works. Environmental awareness needs to be promoted so that humans are not greedy in exploiting nature. In line with this background, the purpose of this study is to examine the form of bucolic, arcadia, as well as retreats and returns in the latest Indonesian novels using Terry Gifford's pastoral theory. For this reason, a descriptive method with a qualitative approach was used. The documentation technique was used to collect data of this study. The Miles and Huberman models were used to analyze the data. The research findings revealed that the latest Indonesian novels deal with narratives that contain environmental wisdom such as bucolics, arcadia construction, and retreat, and return discourses. Therefore, it can be concluded that Indonesian people deal with local wisdom to conserve ecology or environmental preservation. This wisdom is reflected in the culture of the community to protect, keep, and preserve their environment through local culture.